(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
The growth of the social networking phenomenon across the Internet led by social networking sites like Facebook, Twitter and LinkedIn etc. has altered the playing field for business and consumer marketers of all sorts. It is practically impossible to think of a comprehensive marketing strategy in the absence of social networking as one of the key ingredients. In fact, social networking sites have already found a place in every marketers promotion mix today.Human beings have always sought to live in social environments. To a significant level, social networking sites have shifted social networking to Internetand the growth of this medium of networking has been explosive (Vogt &Knapman, 2008). In a short time, these sites have grown from a niche online activity into a phenomenon through which tens of millions of internet users are connected, both in their leisure time, and at work